THE PRESIDENT OF THE REPUBLIC OF UZBEKISTAN AND THEIR SIGNIFICANT CONTRIBUTION TO THE DEVELOPMENT OF THE REPUBLIC OF UZBEKISTAN - Teshaboyeva Nafisa Zubaydulla qizi,; Igor Chekulay Vladimirovich,; G’oyibnazarova Oygul Olloqul qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:this article discusses the Presidents of the Republic of Uzbekistan and their significant contributions to the development of the country. It explains how each leader introduced important political, economic, and social reforms to strengthen independence,  improve  living  standards,  and  modernize  national  institutions.  The article highlights the achievements of the First President, Islam Karimov, who ensured stability  during  the  early  years  of  independence,  created  the  Constitution,  and established strong statehood. It also emphasizes the extensive reforms carried out by President  Shavkat  Mirziyoyev,  who  opened  the  country  to  the  world,  expanded international  cooperation,  and  launched  wide-ranging  modernization  programs.The article  additionally  outlines  progress  in  key  areas  such  as  education,  healthcare, economy, and cultural life under the leadership of Uzbekistan’s presidents. It describes efforts  to  preserve  historical  heritage,  support  youth,  develop  infrastructure,  and promote  innovation  and  digital  technologies.  These  reforms  have  helped  improve social  conditions,  strengthen  national  identity,  and  enhance  Uzbekistan’s  role  in international relations.Overall, the article shows how the presidents of Uzbekistan—through their vision, leadership, and reforms—have contributed to building a strong, independent,  and  rapidly  developing  state  that  successfully  combines  national traditions with modern growth.